Simplified method for performance-based seismic design of suction caissons supporting jacket offshore wind turbines - Antoniou, M.; Kourkoulis, R.; Gelagoti, F.; Anastasopoulos, I. (Soil dynamics and earthquake engineering (1984), 2022)
The paper studies the performance of Offshore Wind Turbines (OWTs) founded on Suction Bucket Jackets (SBJs) in clay under combined wind and seismic loading. A detailed 3D FE model of the soil–foundation–structure (SFS) system is developed and used as a benchmark to assess the efficiency of an enhanced Winkler-based "Caisson-on-Winkler-Soil" (CWS) model, where the soil is replaced by nonlinear hysteretic elements. The proposed CWS model captures residual deformations and hysteresis and offers physical coupling between vertical and moment loading. It allows excellent prediction of the H–M failure envelope in the most relevant first quadrant of H–M space, where the loads act in the same direction. Despite its successful application for the simulation of inertial loading, the CWS model fails to reproduce the dual shearing mechanism that develops at the caisson shaft during shaking, stemming from the combination of kinematic soil shearing due to the vertically propagating shear waves, and shearing due to the superstructure inertial response, thus underpredicting the co-seismic caisson settlements. For the prediction of the latter, the research utilizes spectrum compatible input motions and 3D FE models of varying geometric and material properties to derive linear regression equations that correlate the co-seismic dimensionless settlement of caissons (wE/D) with characteristic dimensional variables of the problem under investigation and the Arias Intensity (IA) of the surface ground motion. As a final step, the paper proposes a hybrid method for performance-based assessment of SBJ OWTs. The proposed method employs the simplified CWS model to calculate the VHM loads and approximately estimate horizontal displacements and rotations at the jacket legs, followed by a preliminary assessment of caisson settlements using the correlations of wE/D with IA, on the basis of spectrum-compatible input motions. •A performance-based seismic assessment method of Suction Bucket Jackets is proposed.•A Winkler-type model is developed, capturing residual deformations and hysteresis.•Permanent caisson deformation under combined wind and seismic loading is explored.•The deficiency of decoupled methods to capture residual settlements is explained.•Caisson settlement is correlated with statistically significant Intensity Measures.